2015
DOI: 10.7727/wimj.2014.149
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Investigations of the Anti-asthmatic Properties of the Aqueous Extract of Justicia pectoralis (Fresh cut)

Abstract: A crude extract of the leaves Justicia pectoralis reduced the formation of histamine-induced wheals in sensitized guinea pigs (p < 0.05) and also reduced histamine-induced tracheal smooth muscle contractions (p < 0.05). It blocked the effect of contraction produced by histamine in the airways; this property supports folklore claims for its use as an antihistamine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 18 publications
0
6
0
4
Order By: Relevance
“…Named popularly as ‘chambá’ in the Brazilian north‐east, this species is useful as expectorant and is in the list of plants potentially useful for phytotherapy purposes according to the Brazilian Health Surveillance Agency (Anvisa) . A few studies reinforce the notion that J. pectoralis can be effective in the respiratory system, and a recent preliminary study revealed potential antiasthmatic properties of an aqueous extract obtained from J. pectoralis by its ability to inhibit histamine‐induced contraction on guinea‐pig trachea …”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…Named popularly as ‘chambá’ in the Brazilian north‐east, this species is useful as expectorant and is in the list of plants potentially useful for phytotherapy purposes according to the Brazilian Health Surveillance Agency (Anvisa) . A few studies reinforce the notion that J. pectoralis can be effective in the respiratory system, and a recent preliminary study revealed potential antiasthmatic properties of an aqueous extract obtained from J. pectoralis by its ability to inhibit histamine‐induced contraction on guinea‐pig trachea …”
Section: Introductionmentioning
confidence: 73%
“…Although the hyper‐responsive phenotype remained observable in OVA‐challenged tracheal tissues maintained in the continuous presence of the extract of J. pectoralis , hyper‐responsiveness was evident only at higher Ca 2+ concentrations in preparations stimulated with ACh or KCl, findings that indicate antispasmodic actions for the extract. Cameron et al . recently reported inhibitory properties of a crude extract of J. pectoralis on guinea‐pig tracheal contractility.…”
Section: Discussionmentioning
confidence: 99%
“…The extract blocked the effect of contraction produced by histamine in the airways [46]. The standardized extract of coumarin from the aerial parts' hydroalcoholic extract of this plant was also tested to evaluate the antiasthmatic properties in male rats previously sensitized by OVA.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the extract was tested on guinea-pig tracheal contraction caused by the cumulative dosing of histamine. Justicia pectoralis reduced histamine-induced tracheal smooth muscle contractions (Cameron et al, 2015).…”
Section: Hedera Helix L -Araliaceae (Leaves)mentioning
confidence: 94%